2022
DOI: 10.1186/s41256-022-00259-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the pre- and post-diagnosis costs of tuberculosis for adults in Pakistan: household economic impact and costs mitigating strategies

Abstract: Background Despite free tuberculosis (TB) care in Pakistan, patients still have to bear high costs, which push them into poverty. This study estimated the pre- and post-diagnosis costs households bear for TB care, and investigated coping mechanisms among adults ≥ 18 years in Karachi, Pakistan. Methods We conducted a cross-sectional study comprising of 516 TB patients identified with completion of at least one month intensive treatment from four pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…The authors also identified an overall average cost of R$283.84 during the pre-diagnosis period and of R$4,161.86 during the post-diagnosis period, which involved not only the patients but also their households. 1 In contrast to previous studies, 4 post-tuberculosis costs were almost 15 times higher than were pre-tuberculosis costs, and that was mostly attributed to non-medical direct and indirect costs, including loss of income in 60% of cases.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The authors also identified an overall average cost of R$283.84 during the pre-diagnosis period and of R$4,161.86 during the post-diagnosis period, which involved not only the patients but also their households. 1 In contrast to previous studies, 4 post-tuberculosis costs were almost 15 times higher than were pre-tuberculosis costs, and that was mostly attributed to non-medical direct and indirect costs, including loss of income in 60% of cases.…”
mentioning
confidence: 57%
“…However, most studies regarding financial issues related to tuberculosis address costs during pre-diagnosis, diagnosis, and treatment, leaving aside post-disease losses. 3 , 4 …”
mentioning
confidence: 99%
“…During a patient's hospital stay, the cost of food and accommodation for the caregiver significantly increases, along with the indirect cost of the caregiver's absence from the work. Patients with a history of hospitalization also had higher medical and family care costs [ 37 ]. In addition, a hospitalized patient had a more severe condition, so the indirect costs increased accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The out‐of‐pocket healthcare expenditure can be significant for TB taking into consideration factors such as the need to sometimes buy the antibiotics and the long duration of treatment. A study by Razzaq et al estimated the pre‐ and post‐diagnosis cost of TB which came out to be 63.8 USD pre‐diagnosis, 24 USD after diagnosis, 10.5 USD for treatment, and 349 USD for hospitalization 39 . Moreover, according to a cross‐sectional survey in 2020, the median cost of TB in Pakistan was found to be approximately 360 USD and around 67% of patient's households were affected by the catastrophic costs, especially if the patient is the sole bread earner of the house as the treatment led to unpaid sick leaves and even loss of job 40 .…”
Section: Susceptibility Of Extrapulmonary Tb In South Asiansmentioning
confidence: 99%
“…27 USD for treatment, and 349 USD for hospitalization. 39 Moreover, according to a cross-sectional survey in 2020, the median cost of TB in Pakistan was found to be approximately 360 USD and around 67% of patient's households were affected by the catastrophic costs, especially if the patient is the sole bread earner of the house as the treatment led to unpaid sick leaves and even loss of job. 40…”
Section: Eptb Manifestations Are Observed In Children Inmentioning
confidence: 99%